Skin Manifestations of COVID-19 Infection in the Practice of Dermatologist - S. R. Senchukova; Yu. M. Krinitsyna; D. A. Mikhailova (Архивъ внутренней медицины)
In early 2020, the World Health Organization announced the emergence of the disease-a new coronavirus infection (COVID-19). High contagiousness and asymptomatic transmission of the virus led to a rapid spread of infection and reached the scale of a pandemic. It was found that the SARSCoV-2 virus is pathogenic to the lower respiratory tract. At the same time, there are extrapulmonary manifestations, including skin rashes, which are characterized by an extreme variety. Some authors describe skin lesions as the first, and sometimes the only, symptom of a new coronavirus infection. Thus, skin manifestations should be carefully evaluated by dermatologists during the examination, especially during the ongoing pandemic.This article presents 6 clinical cases with various skin manifestations in the acute period of COVID-19 infection. The first patients to complain were dermatologists. Rashes on the skin are characterized by a variety and prevalence: polymorphic vasculitis, livedo-angiitis, urticary, spot-papular, papu lo-vesicular, papulo-squamous elements. All cases are united by the presence of the main symptoms of coronavirus infection characteristic of the acute period — hyperthermia, headache, fatigue, myalgia, partial or complete anosmia, ageusia.Thus, the exchange of clinical experience of skin manifestations in COVID-19 infection is extremely relevant during the ongoing pandemic. The analysis of the accumulated data will provide an understanding of the diagnostic significance and the ability to assess the prognosis when observing such patients.